2022
DOI: 10.1111/hepr.13867
|View full text |Cite
|
Sign up to set email alerts
|

Automated image analysis of keratin 7 staining can predict disease outcome in primary sclerosing cholangitis

Abstract: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease that can lead to liver cirrhosis or cholangiocarcinoma. Here, we developed a K7-AI model 2.0 to analyze K7-stained liver specimens of patients with PSC. We found that the K7-AI model 2.0 can serve as a prognostic tool for clinical endpoints, since it was able to provide significant information on disease outcomes based on different histological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“… 34 , 35 Other studies have reported DR to be associated with higher MELD scores in alcoholic hepatitis and high alkaline phosphatase levels in primary biliary cholangitis. 32 , 36 DR also predicted the development of cholangiocarcinoma and liver-related death in primary sclerosing cholangitis 22 as well as overall survival in patients with hepatitis C cirrhosis and alcoholic hepatitis. 34 , 37 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 34 , 35 Other studies have reported DR to be associated with higher MELD scores in alcoholic hepatitis and high alkaline phosphatase levels in primary biliary cholangitis. 32 , 36 DR also predicted the development of cholangiocarcinoma and liver-related death in primary sclerosing cholangitis 22 as well as overall survival in patients with hepatitis C cirrhosis and alcoholic hepatitis. 34 , 37 …”
Section: Discussionmentioning
confidence: 94%
“… 18 20 A recently published image-processing neural network of K7-stained liver sections developed for primary sclerosing cholangitis showed improved performance in identifying various DR components with accuracy beyond the reach of manual scoring and enhanced prognostic value. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Consistently with the aforementioned study, all patients in our cohort with data on prior imaging had advanced CCA. Altogether, these results argue against the efficacy of imaging-based screening for iCCA in patients with PSC and, consequently, emphasise the need for new screening modalities, e. g., anti-glycoprotein (GP) 2-IgA, bile and urine proteome analysis, next-generation sequencing, or protein biomarkers containing serum extracellular vesicles [4,14,15,16]. Whereas liver transplantation in carefully selected patients with pCCA, e. g., patients with unresectable tumours or tumours in PSC, with a diameter < 3 cm, after neoadjuvant therapy, and in the absence of intrahepatic or extrahepatic metastasis may be considered a therapeutic option, iCCA is widely considered a contraindication for liver transplantation because of high recurrence rates and reduced long-term survival [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with the aforementioned study, all patients in our cohort with data on prior imaging had advanced CCA. Altogether, these results argue against the efficacy of imaging-based screening for iCCA in patients with PSC and, consequently, emphasise the need for new screening modalities, e. g., anti-glycoprotein (GP) 2-IgA, bile and urine proteome analysis, next-generation sequencing, or protein biomarkers containing serum extracellular vesicles [4,14,15,16].…”
Section: Uicc Stage T N Mmentioning
confidence: 99%